Diseño del sistema de gestión de seguridad y salud en el trabajo para la empresa Estialambres Kirios (2021)
The project carried out is the design of an Occupational Health and Safety System (OSH), based on the provisions of the Only Regulatory Decree 1072 of 2015, chapter 6, for the enterprise Estialambres Kirios located in the municipality of Bello-Antioquia, with the aim of generating controls that help minimize the occupational risks associated with the processes conducted in the organization. The proposal was developed in three phases: first, the initial evaluation to determine the current workplace health and safety problems of the company; second, analysis for data collection through a checklist, verifying compliance with resolution 0312 of 2019 and thus accurately determining non-compliance in relation to the minimum requirements; and finally the definition and design of the necessary documents in accordance with the PHVA cycle to control and improve the shortcomings found. The implementation of the proposed system will allow the company to comply with the legislation and will be positively impacted by reducing absenteeism due to accidents and occupational diseases.